pymetamodels: A Python package for metamodeling and design automation - Nicolas Escribano; José Manuel Bielsa; Francisco Lahuerta (SoftwareX, 2024)
The pymetamodels package provides a comprehensive suite of machine learning (ML) metamodeling and analysis tools for the virtual development of modeling systems within a unified and accessible Python framework. This package support ML applications in materials science, material informatics, and the construction of metamodels for materials, components, and systems, informed by rigorous physics based modeling (continuum, mesoscopic) and experimental characterization data. The pymetamodels Python package streamlines the creation of multivariate problem workflows encompassing sampling analysis, sensitivity analysis, metamodel training, optimization solution, model calibration, and design optimization implementations through the metamodel-assisted design optimization (MADO) approach.